FACTORS AFFECTING THE CRIMINAL ACT OF COMMERCIAL SEXUAL EXPLOITATION OF CHILDREN (ESKA) IN THE COASTAL AREA OF BANDAR LAMPUNG CITY - Ardiansyah, Joni; Rosidah, Nikmah; Achmad, Deni (Sriwijaya Crimen and Legal Studies, 2024)
Commercial sexual exploitation of children (ESKA) is a fundamental violation of children's rights. The offense is in the form of sexual violence by an adult with remuneration to a child, a third person, or other persons. ESKA treats children treated as commercial sexual objects. The problem in this study is what are the factors that affect the crime of Commercial Sexual Exploitation of Children (ESKA) in the coastal area of Bandar Lampung? This study uses normative legal methods. The results obtained are the factors that influence the crime of Commercial Sexual Exploitation of Children (ESKA) in the coastal area of Bandar Lampung, which can be seen by the poor people so that people make this activity a job to meet their living needs. The suggestion in this study is that there must be good coordination between law enforcement officers and the government to prevent the occurrence of criminal acts of Commercial Sexual Exploitation of children from recurring, such as providing decent work and conducting educational activities to the public about criminal acts of Commercial Sexual Exploitation of children. The community must also be able to be open and cooperate with all relevant parties to prevent the re-occurrence of criminal acts of Commercial Sexual Exploitation of children.